Home Rule, Democracy and the Unmaking of the United Kingdom, 1885-1921 - Eugenio Biagini (Revue Française de Civilisation Britannique)
From 1885 to 1921 United Kingdom politics were polarized around the question of parliamentary devolution for Ireland (Home Rule). A major argument against Home Rule was that it would have been incompatible with the survival of the British Empire and indeed of the United Kingdom, because sovereignty could not be divided. However, Home Rule supporters insisted that the proposal was in the Irish national interest. This claim was in itself divisive in Ireland, as well as within the United Kingdom as a whole, and set the South against Ulster, which by 1912 was (literally) up in arms against any idea of weakening or diluting the Union with Britain. By 1887 Liberals in both Scotland and (soon afterwards) in Wales started to campaign for their own form of Home Rule. Ostensibly only an ‘Irish’ question, Home Rule was in fact the beginning of a wider debate about the governance of the United Kingdom and the tension between a centralized political system and the claims of ethnic groups and distinct regions in a multi-national state. This article examines the wider significance of the crisis in the constitutional rebalancing of a liberal, but still undemocratic, state. It will start from the time when the British system was at its apex, between 1707 and 1885. In this period parliament provided social and cultural legitimacy for the centralization of power and created cohesion for the wider imperial project. Second, this article focuses on the advent of democracy from 1885, and the way the latter made it more difficult for parliament to agree on the ‘national’ interest – especially when the latter depended on finding common ground between four nations.